TrimetaziDine as a Performance-enhancING drug in heart failure with preserved ejection fraction (DoPING-HFpEF): rationale and design of a placebo-controlled cross-over intervention study - A. A. van de Bovenkamp; A. J. Bakermans; C. P. Allaart; A. J. Nederveen; W. E. M. Kok; A. C. van Rossum; M. L. Handoko (Netherlands Heart Journal, 2020)
Abstract Background Currently, no specific treatment exists for heart failure with preserved ejection fraction (HFpEF). Left ventricular (LV) relaxation during diastole is a highly energy-demanding process, while energy homeostasis is known to be compromised in HFpEF. We hypothesise that trimetazidine – a fatty acid β‑oxidation inhibitor – improves LV diastolic function in HFpEF, by altering myocardial substrate use and improving the myocardial energy status. Objectives To assess whether trimetazidine improves LV diastolic function by improving myocardial energy metabolism in HFpEF. Methods The DoPING-HFpEF trial is a randomised, double-blind, placebo-controlled cross-over intervention trial comparing the efficacy of trimetazidine and placebo in 25 patients with stable HFpEF. The main inclusion criteria are: New York Heart Association functional class II to IV, LV ejection fraction ≥50%, and evidence of LV diastolic dysfunction. Patients are treated with one 20-mg trimetazidine tablet or placebo thrice daily (twice daily in the case of moderate renal dysfunction) for two periods of 3 months separated by a 2-week washout period. The primary endpoint is the change in pulmonary capillary wedge pressure during different intensities of exercise measured by right heart catheterisation. Our key secondary endpoint is the myocardial phosphocreatine (PCr)/ATP ratio measured by phosphorus-31 magnetic resonance spectroscopy and its relation to the primary endpoint. Exploratory endpoints are 6‑min walk distance, N -terminal pro-brain natriuretic peptide levels, and quality of life. Conclusion The DoPING-HFpEF is a phase-II trial that evaluates the effect of trimetazidine, a metabolic modulator, on diastolic function and myocardial energy status in HFpEF. [EU Clinical Trial Register: 2018-002170-52; NTR registration: NL7830]